A preliminary study on in vitro evaluation of antiviral properties of bird nest extract against animal coronavirus - Sepiri, Muhammad Daud Derwin; Arshad, Siti Suri; Mehrbod, Parvaneh; Awang Isa, Mohd Kamaruddin; Bande, Faruku; Abu, Jalila; Abdul Kadir, Fadzilah A'ini (2012)
Bird’s nest has become a commodity in Peninsular Malaysia and other regions in South East Asia. The nest is made up of the bird’s saliva during nesting. There are several common species of swiftlet such as the Aerodramus fuciphagus, Aerodramus maximus and Apus pacificus. Malaysia is the second largest producer of bird nest in the world.The nesthas been used for many years as remedy as well as traditional medicine and is common among the Chinese worldwide. The nest is allegedly able to curea wide range of ailments ranging from enhancing complexion, alleviating asthma, and strengthening the immune system (1). However, the antiviral efficacy studies of bird nest are lacking on viral diseases except a study on influenza virus. Preliminary study shows that the bird nestis able to neutralize influenza viruses and inhibit the agglutination of erythrocytes (2). This preliminary research is to examine if the bird nest extract has antiviral properties against the feline infectious peritonitis virus in vitro.